1990
DOI: 10.1002/art.1780330704
|View full text |Cite
|
Sign up to set email alerts
|

Hla‐dr alleles with naturally occurring amino acid substitutions and risk for development of rheumatoid arthritis

Abstract: To determine the HLA‐DR4 subtypes associated with rheumatoid arthritis (RA), we performed amplification of DR4 DRB1 genes by the polymerase chain reaction and dot‐blots with oligonucleotide probes. In 52 HLA‐DR4+ RA patients, Dw4 was the predominant subtype. This subtype was found in 45 of 52 patients (86.5%) compared with 33 of 59 DR4+ controls (55.9%; P < 0.001). In the whole population, Dw4 also gave the highest relative risk for RA (RR = 5.31). Relative risk was also associated with DR1.1, the common white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 34 publications
4
41
0
3
Order By: Relevance
“…DNA analysis. Genomic DNA was isolated from peripheral blood mononuclear cells as described (13,14). DRB1 alleles were amplified by a polymerase chain reaction (PCR) with the following primers: HLA-DRl, TTGTGGCAGCTTAAGTTTGAA Oligonucleotide hybridization of amplified DNA.…”
Section: Methodsmentioning
confidence: 99%
“…DNA analysis. Genomic DNA was isolated from peripheral blood mononuclear cells as described (13,14). DRB1 alleles were amplified by a polymerase chain reaction (PCR) with the following primers: HLA-DRl, TTGTGGCAGCTTAAGTTTGAA Oligonucleotide hybridization of amplified DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The filters were hybridized to 32P-endlabeled SSO probes and visualized after exposure to x-ray film (XARJ; Eastman-Kodak, Rochester, NY). The SSO probes used were as described by Gao et al (9) and included PS-4 (Dw4, covering codons 68-74), PS-5 (DwlO, codons 69-75), and PS-7 (Dwl5, codons 54-60). All oligonucleotides were synthesized by Oligos Etc.…”
Section: Methodsmentioning
confidence: 99%
“…24,25 Later the associated sequences were shown to be from position 70-74 (QKRAA, QRRAA, RRRAA). Following Gao's proposal, 26 du Montcel et al 27 proposed a new classification based on the hypothesis that amino acids at position 70 or 71 could confer a different risk when coupled with the common RAA sequence. Indeed, she demonstrated that given the role of the RAA sequence (72-74), a lysine (K) at position 71, thus the sequence KRAA at position 71-74, confers the highest risk, with a lower risk in sequence made by the sequences RRRAA and QRRAA.…”
Section: G Ferraccioli Et Almentioning
confidence: 99%